Caracterización de los límites naturales: un caso del área de Chroberz (Polonia Centro-Meridional) - Kulczyk, Sylwia (M+A. Revista Electrónica de Medioambiente, 2006)
The article presents the study of character of landscape boundaries in south-east Poland, within the upland loess and gypsum landscape and within the landscape of valleys’ bottoms. The investigated boundaries occurred as the effect of lithological, morphometrical and land use changes. The methods of description of 3 structural and 2 functional features have been described. These are length, contrast, visibility, permeability and stability. Some correlations between functional and structural features have been stated. It is proposed to implement stated relativities in the process of spatial planning.
Keywords: Landscape boundary; Structure and functioning of landscape